Expansión e internacionalización de las pymes agroindustriales colombianas (2005)
This paper presents several topics about the problems in different contexts faced by the colombian small and medium sized enterprises (SMEs) of the agricultural sector as a part of the research study the author is working in. During the research in the SMEs in the city of Bogotá and after revised in an exhaustive way an extensive literature, it has reaching different solutions and tools to solve the internacionalization problem of them, starting with the status today at the national and international level. This article focuses in four tools to overcome the weakness of export culture of the sector.